2015
DOI: 10.1371/journal.pone.0136908
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Profiles in Patients with Type-1 Autoimmune Hepatitis

Abstract: Recent studies have demonstrated that micro (mi)RNA molecules can be detected in the circulation and can serve as potential biomarkers of various diseases. This study used microarray analysis to identify aberrantly expressed circulating miRNAs in patients with type 1 autoimmune hepatitis (AIH) compared with healthy controls. Patients with well-documented and untreated AIH were selected from the National Hospital Organization (NHO)-AIH-liver-network database. They underwent blood sampling and liver biopsy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 40 publications
1
71
2
1
Order By: Relevance
“…This may reflect the fact that the duration of miRNA‐21 upregulation during the course of HCV infection was variable since the time of HCV infection is certainly not known precisely for each patient. Migeta et al have documented a positive correlation between miRNA‐21 and both ALT and AST. They reported that serum miRNA‐21 levels may be related to liver damage activity of HCV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may reflect the fact that the duration of miRNA‐21 upregulation during the course of HCV infection was variable since the time of HCV infection is certainly not known precisely for each patient. Migeta et al have documented a positive correlation between miRNA‐21 and both ALT and AST. They reported that serum miRNA‐21 levels may be related to liver damage activity of HCV.…”
Section: Discussionsupporting
confidence: 92%
“…However, serum albumin level and platelets count showed a statistically significant increase among HCV patients after receiving treatment. These results were in accordance with Migita et al, who have proposed that the upregulated expression of miRNA‐21 may be due to increased proliferation of liver cells during HCV infection. Additionally, the current study declared an inverse relation between miRNA‐21 and the viral load.…”
Section: Discussionmentioning
confidence: 98%
“…MiR‐122 modulates hepatic production of cholesterol and lipoproteins . Plasma levels of miR‐122 have also correlated with serum aminotransferase levels in patients with liver disease , and the level of miR‐122 in graft perseveration fluid has been associated with early graft loss after liver transplantation . These findings have supported the consideration of miR‐122 as a biomarker of liver injury .…”
Section: Resultsmentioning
confidence: 81%
“…Plasma levels of miR‐122 have also correlated with serum aminotransferase levels in patients with liver disease , and the level of miR‐122 in graft perseveration fluid has been associated with early graft loss after liver transplantation . These findings have supported the consideration of miR‐122 as a biomarker of liver injury . Both miR‐21 and miR‐122 have been increased in the circulation of patients with autoimmune hepatitis .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation